RESPON TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir) TERHADAP PEMBERIAN PUPUK KOTORAN SAPI - Telaumbanua, Atap Niat; Adiwirman, Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the response of water spinach plants to the implementation of cow manure and to determine the best dosage of cow manure for water spinach (Ipomoea reptans Poir) which provides the highest growth and yield. This research was conducted at the University of Riau's Faculty of Agriculture Experimental Station, starting from February 2018 to April 2018. This study used a Randomized Block Design (RBD) consisting of 5 doses of cow manure treatment and 4 replications. The treatments was tested K0 (0 t.ha-1), K1 (5 t.ha-1),  K2 (10 t.ha-1),K3 (15 t.ha-1), K4 (20 t.ha-1). The parameters observed were plant height, leaf number, leaf area, fresh weight per plant, root to shoot ratio and dry weight per plant. Data were analyzed using variance and continued with HSD test level of 5%. The results showed that the administration of cow manure with a dose of 20 t.ha-1 gave the highest results in almost all observational parameters, namely plant height (31.33 cm), number of leaves (13.15 cm), leaf area (18.65 cm2), root canopy ratio (9.21), dry weight per plant (5.15 g) except fresh weight per plant (21.75 g). Keywords:Ipomoea reptans Poir, cow manure